ANALYSIS OF DETERMINANTS AFFECTING INCOME OF ARTISANAL FISHERMEN IN TEGAL CITY - Mudzakir, Abdul Kohar; Boesono, Herry; Harahap, Husnul Yaqin (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
The fisheries sector, especially capture fisheries, is the leading sector in Tegal City. Fisheries activities in Tegal City are concentrated in the Tegalsari Coastal Fishery Port (PPP) where the majority of the perpetrators are small fishermen. Traditional fishermen who are artisanal fishermen generally live below the poverty line. Based on data from the Department of Maritime Affairs and Fisheries of Tegal City in 2014, almost 12,589 people worked as fishermen, consisting of 630 people as skippers or ship owners and 11,959 as fishermen workers or crew members (ABK). The low income of traditional fishermen is a long-standing problem, but it has not been resolved until now. The purpose of this study was to analyze the factors that affect the income of small fishermen in Tegal City. The types of data used in this study are primary and secondary data. Primary data was obtained by distributing questionnaires to respondents, while secondary data was obtained by studying literature relevant to the research. Respondents in this study were determined through purposive sampling as many as 140 respondents. Data analysis in this study used multiple linear regression analysis with the help of SPSS 22 software. The results showed that of the 4 independent variables studied (age, education, number of family dependents, and total expenditure) it was found that 2 factors significantly influenced the income level of small fishermen in Indonesia. Tegal City, namely the number of family dependents and total expenses